Srovnání strategických plánů ekonomického rozvoje ve městech České republiky, Slovenska, Ukrajiny a Rumunska - Myšková, Hana (Univerzita Pardubice, 2006)
Diplomová práce se zaměřuje na objasnění pojmu strategického plánování ekonomického rozvoje, zejména jeho procesu. Praktická část se zabývá popisem dvaceti vybraných měst a mikroregionů, analýzou problémů označených ve strategických plánech a zejména komparací navrhovaných způsobů řešení těchto problémů. V závěru jsou označeny některé nedostatky a doporučení pro strategické plánování v budoucnosti.

Diploma work concerns on the problem of strategic planning, especialy on the process of strategic planning. The main part deals with description of twenty analyzed cities and microregions, characteristic of problems encountered in strategic plans, and comparation of proposed solutions. In conclusion some deficiencies and recommendations are mentioned for future strategic planning.
Comparison of strategic plans of economic development in the cities of the Czech republic, Slovakia, Romania and Ukraine.
Keywords: Strategic Planning; Business; Transportation; Human Resources; Investments; tourist industry; strategické plánování; Podnikání; Doprava; Lidské zdroje; Investice; Cestovní ruch